Morphology and reproductive strategies of the gametophyte of Polypodium lepidotrichum (Fée) Maxon (Polypodiaceae) - Reyes Jaramillo, Irma; Perez-Garcia, Blanca (Instituto de Ecología, A.C., 1994)
The young prothallus of Polypodium lepidotrichum (Fée) Maxon is a short filament with four to five cells. Later on, the thallus is spathulate. The mature thallus, about eight weeks after germination, is cordate, reniform or ovate with a narrow base. Bisexual and unisexual gametophytes were produced. Young sporophytes were observed twelve weeks after the spore were sown. It is concluded that the reproductive strategies of P. lepidotrichum include intragametophytic and intergametophytic fertilization.